PENGARUH WORD OF MOUTH (WOM), CITRA MEREK, DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN MEMILIH KULIAH: STUDI KASUS PADA MAHASISWA ITSKES MUHAMMADIYAH SELONG - Hartiani, Hartiani; Yuniarti, Ratna; Zainuddin, Muhammad (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The increase in the number of students every year nationally is an opportunity and challenge for universities (PT) to be able to capture the interest of new students, in order to determine the decision to choose to study at the campus in question. The purpose of this study is to see the influence of word of mouth (WOM), reference groups, and brand image on the decision to choose college. This research was conducted on ITSKes Muhammadiyah Selong, East Lombok, West Nusa Tenggara, Public Administration Study Program. The sample in this study is 95 people. The sampling technique used is purposive sampling. The results of data analysis showed that the Word of Mouth (WOM) variable had a nonsignificant effect on the decision to choose a college, but WOM had a significant effect on the decision to register through brand image. Likewise, the reference group variable had a non-significant effect on the selection decision, and the reference group had a significant effect on the choice decision mediated by the brand image. On the direct influence, brand image has a positive and significant effect on the decision to choose to study at ITSKes Muhammadiyah Selong